Predicting, monitoring, and assessing forest fire dangers and risks - Baranovskiy, Nikolay Viktorovich, 1978- (Advances in environmental engineering and green technologies (AEEGT) book series., 2020)
"This book examines current research on predicting, monitoring, and assessing forest fire dangers and risks"--